Determination of the Kinetic Parameters for 123I Uptake by the Thyroid, Thyroid Weights, and Thyroid Volumes in Present-day Healthy Japanese Volunteers. Issue 4 (April 2020) - Kudo, Takashi; Inano, Akihiro; Midorikawa, Sanae; Kubo, Hitoshi; Hayashi, Kino; Nakashima, Sawako; Fukushima, Chizu; Maeda, Kazuya; Oriuchi, Noboru; Irie, Shin; Yamashita, Shunichi; Kusuhara, Hiroyuki
Abstract : Abstract: The purpose of this study was to evaluate the kinetic parameters that determine the uptake rate of radioiodide in the thyroid over 24 h after administration and to estimate thyroid volumes/masses of present-day Japanese. Methods: We determined the thyroid uptake rate of 123 I in healthy male Japanese after oral administration (4.5–8.0 MBq) without iodine restriction. Masses of thyroid glands were collected in 2012–2016 during autopsies of 7, 651 male and 3, 331 female subjects. Volumes of thyroid glands were estimated by ultrasonography and magnetic resonance imaging in 52 male subjects. Results: The thyroid uptake rate of 123 I for 24 h was 16.1 ± 5.4%. Kinetic model analysis was conducted to obtain the clearances (L h −1 ) for thyroid uptake and urinary excretion of 123 I (0.499 ± 0.258 and 2.10 ± 0.39 L h −1, respectively). The masses of thyroid glands were on average 19.8 g (95% confidence interval of 18.3−19.5 g) and 15.5 g (95% confidence interval of 14.7−16.2 g) in male and female subjects aged 19–52 y, respectively. Volumes of thyroid glands estimated by ultrasonography and magnetic resonance imaging were 17.5 ± 5.2 and 14.2 ± 5.3 mL, respectively. In healthy Japanese, there has been no significant change for at least 50 y in the thyroid uptake of radioiodide over 24 h or in its kinetic parameters. These Japanese-specific kinetic parameters will allow quantitative estimation of the radiation exposure from the Fukushima accident and its variance during the individual's evacuation from or stay in Fukushima. Abstract : Supplemental digital content is available in the text.